Dosimetric comparison of TomoDirect, helical tomotherapy, and volumetric modulated arc therapy for postmastectomy treatment - Wannapha Nobnop (2020)
© 2020 The Authors. Journal of Applied Clinical Medical Physics published by Wiley Periodicals, Inc. on behalf of American Association of Physicists in Medicine. Purpose: To compare dose to the targets and organs at risk (OARs) in different situations for postmastectomy patients who require radiation to the chest wall with or without regional nodal irradiation when using three treatment techniques. Methods and materials: Thirty postmastectomy radiotherapy (PMRT) patients previously treated by helical tomotherapy (HT) at our institution were identified for the study. The treatment targets were classified in three situations which consisted of, the chest wall (CW) only, the chest wall plus supraclavicular lymph nodes (CW + SPC), and the chest wall plus supraclavicular and whole axillary lymph nodes irradiation (CW + SPC+AXLN). The volumetric modulated arc therapy (VMAT) plans and Tomodirect (TD) plans were created for each patient and compared with HT treatment plans which had been treated. The target coverage, dose homogeneity index (HI), conformity index (CI), and dose to OARs were analyzed. The quality scores were used to evaluate the appropriate technique for each situation from multiparameter results. Results: The HT and VMAT plans showed the advantage of target coverage and OARs sparing for the chest wall with regional nodal irradiation with the higher plan quality scores when compared with TD plans. However, TD plans demonstrated superiority to contralateral breast sparing for the chest wall without regional nodal situation reaching the highest of planned quality scores. HT plans showed better HI, CI, and target coverage (P < 0.01) than TD and VMAT plans for all patient situations. Volumetric modulated arc therapy plans generated better contralateral breast and heart sparing at a lower dose than HT. Conclusion: The arc-based techniques, HT and VMAT plans, provided an advantage for complex targets in terms of target coverage and OARs sparing. However, the static beam TD plan was superior for contralateral organ sparing meanwhile achieving good target coverage for the chest wall without regional node situations.